TECHNIQUES OF ECONOMIC VALUATION OF ENVIRONMENTAL GOODS - vapa tankosic, jelena (International Journal of Economic Practice and Policy, 2024)
Many companies in the environmental goods sector are interested in creating "added value". When looking at the viability of investing in production, companies starting out the production in the environmental goods sector should research production costs as well as consumer demand for new environmental products. Although the costs of environmental goods production can be roughly estimated, estimating consumer demand is a complex process. Questions related to determining the price of a new environmental goods product, the level of demand, the target segment and identifying consumer needs, which are inevitably present when introducing an new product to the market, represent the starting point for creating an adequate marketing strategy. This paper aims to explore the techniques of economic valuation of environmental goods as well as the concept of "Willingness to pay" for environmental goods or services. The paper shall analyze two basic groups of economic valuation techniques: revealed preferences techniques (RP), which observe consumer behavior and their choices on the real market, and stated preferences techniques (SP).
Keywords: economic valuation; environmental goods; willingness to pay; revealed preferences; stated preferences